Imaging techniques in Veterinary Medicine. Part I: Radiography and Ultrasonography. (2021) - Meomartino, Leonardo; Greco, Adelaide; Di Giancamillo, Mauro; Brunetti, Arturo; Gnudi, Giacomo
Abstract: In Veterinary Medicine all the Imaging techniques are used and described but, due to organizational, managerial and, mostly, economical reasons, Radiography and Ultrasonography are the most used. Veterinary Radiology teaching has a relatively small number of educational credits in the degree courses but, nowday, educational opportunities are remarkably increased thanks to a number of post-degree courses and masters, organized both by the universities and private veterinary associations. The relevance of Diagnostic Imaging is particularly true in Veterinary Medicine, in which Radiology could be considered "indispensable" for diagnosis, prognosis and follow up. Furthermore, it should not be forgotten that the diagnostic image represents a "document" and, has a relevant role in legal medical debats. In this first part, Radiography and Ultrasonography are described.